The Venture Capital Deformation Value Destruction throughout the Investment Process - Klonowski, Darek (Springer International Publishing, 2018)
In spite of the robust development of venture capital that has occurred over the last three decades, returns from venture capital have been declining. This book focuses on a simple question: why? The answer lies in the context of multiple deformations that have occurred throughout the venture capital process. The book critically assesses the ways in which interactions between different stakeholders in the venture capital ecosystem change (or "deform") venture capital, decreasing its value. Klonowski also reveals that venture capital actually has few benefits-and some outright disadvantages-for entrepreneurs, and it can create a self-perpetuating cycle of investment and loss for the entire venture capital industry. This is especially true as corporate governance and compensation structures may create significant misalignments, incongruities, and conflicts of interest between general and limited partners.